Microbial and sensory evaluation of Bangladeshi frozen chicken sausage (Asian Journal of Medical and Biological Research, 2016)
The purpose of this study was to evaluate the microbiological safety and the effect of some synthetic chemicals with comparison to natural additives such as rosemary extract in preventing microbial growth and as a source of antioxidant by maintaining GHP as well as GMP of Bangladeshi processed chicken sausages with low fat content to correlate some scientific evidence in producing cancer and cardiovascular diseases by the consumption of meat product. Two experimental batches of chicken sausage were prepared according to Bangladeshi standard using different parameters of ingredients. Then centesimal parameter, PH and instrumental color of the product were analyzed according to standard protocol. A sensory parameter was also checked by ranking the acceptance level of consumers about different batches of chicken sausage. The sensory properties and the instrumental color parameter of two experimental batches of chicken sausage A and B were found almost similar in comparison to the commercial cured chicken sausage C but quite dissimilar in comparison to commercial uncured sausage D. Total coliforms were observed 4.4 × 10 for sausage A and 5.3 × 10 for sausage B, while the most probable number (MPN) for E. coli was 1.7 for both products. The counting of sulphite reducing Clostridium was 2 cfu/g and 3 cfu/g for both of the batches A and B consecutively. The coagulase-positive Staphylococci and lactose fermenting Salmonella was not found in any batches of chicken sausage.The results of this experiment clearly mentioned the possibility of producing safe and high quality chicken sausage with reduced fat content in Bangladesh by using natural pigments and antioxidants.Asian J. Med. Biol. Res. December 2015, 1(3): 463-470